2019
DOI: 10.1111/jora.12491
|View full text |Cite
|
Sign up to set email alerts
|

Giving to Friends, Classmates, and Strangers in Adolescence

Abstract: This study examined how perspective taking and sensitivity to social rewards predict giving to friends, classmates, and strangers in adolescence. Five hundred and twenty adolescents aged 12–17 years completed questionnaires on perspective taking and social rewards and played three Dictator Games in which they divided coins between themselves and a friend, classmate, and stranger. We found that, irrespective of age, adolescents donated most to a friend, less to their classmate, and least to a stranger, and fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 17 publications
3
12
0
Order By: Relevance
“…In line with previous studies, we found that girls shared more with an anonymous other than boys across the studied period (Fehr et al, 2013;Gummerum et al, 2008;van de Groep et al, 2019). We extend these findings by showing that girls also shared more with a best friend and disliked peer compared to boys during the elementary school.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In line with previous studies, we found that girls shared more with an anonymous other than boys across the studied period (Fehr et al, 2013;Gummerum et al, 2008;van de Groep et al, 2019). We extend these findings by showing that girls also shared more with a best friend and disliked peer compared to boys during the elementary school.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to other studies, we found level differences in sharing with different recipients (Güroglu et al, 2014;Lu & Chang, 2016;Moore, 2009;Paulus & Moore, 2014;van de Groep et al, 2019;Yu et al, 2016). Our findings together with previous studies underscore that children use social contextual information during their sharing decisions (Güroglu et al, 2009;van de Groep et al, 2019;.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations